Common Fixed Points of (α,η) − (θ,ϝ) Rational Contractions with Applications - Mujahid Abbas; Hira Iqbal; Manuel De La Sen (Journal of Mathematics)
We present the notion of set valued (α,η)-(θ,ϝ) rational contraction mappings and then some common fixed point results of such mappings in the setting of metric spaces are established. Some examples are presented to support the concepts introduced and the results proved in this paper. These results unify, extend, and refine various results in the literature. Some fixed point results for both single and multivalued (θ,ϝ) rational contractions are also obtained in the framework of a space endowed with partial order. As application, we establish the existence of solutions of nonlinear elastic beam equations and first-order periodic problem.